The Need for Innovative Activity of Preschool Educational Institution Teachers in Educating a Healthy Generation - Boymurodova., G. T.; Jurayeva, D. U. (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article the need for innovative activities of preschool educators in raising a healthy generation, socio-cultural, intellectual and moral capabilities of the educator, regular self-development of the educator pedagogue and improvement of the preschool education system consists of forming nikma and skills. In this sense in the article the need for innovative activities of preschool educators purpose is analyzed.